Globalisasi dan Resistensi: Studi Kasus Kemunculan Gerakan Occupy Wallstreet - S.M., Dias Pabyantara (Global and Policy Journal of International Relations, 2020)
The main globalist argument is to depict globalization as a universalization process. The notion chains several debates on how the future of resistance takes place within globalization. The interconnectivity, which became the main feature of the recent globalization, issues a dominant narrative concerning universal governance in the form of capitalism. Those dominant narrative results in an inevitable globalization paradigm. On the other hand, the skeptic critics stated that interconnectivity made possible towards resistance upon globalization in terms of relations between market and state. This research departs from the skeptic notions of globalization to argue that there is a robust future of resistance and ideology along with the globalization process. Globalization brought up a discussion concerning the nature of the paradox of power, which lies beneath interconnectivity. On the one hand, interconnectivity connects the capitalist impacting the hegemon nature of nowadays capitalism. On the other hand, the hegemony caught up in a vis-a-vis position with the ideological resistance in the Occupy Wallstreet movement.Keywords: Globalization, Resistance, Occupy Wallstreet Movement, Power, InterconnectivityArgumen kaum globalis yang mengidentifikasi globalisasi sebagai proses universalisasi memunculkan perdebatan mengenai eksistensi resistensi. Di satu sisi, interkoneksi dalam globalisasi memunculkan narasi mengenai standar tata kelola nilai yang seragam. Sehingga dimensi ideologi didominasi oleh pemilik modal melalui paham kapitalisme. Konsekuensinya, globalisasi dalam kerangka kapitalisme global dimaknai sebagai proses tunggal yang tidak mungkin dihindari. Di sisi lain, kaum skeptis menyatakan interkoneksi dalam globalisasi justru memfasilitasi munculnya struktur perlawanan terhadap narasi tunggal globalisasi. Interkoneksi dalam globalisasi memungkinkan pengorganisaan gerakan perlawanan dari akar rumput, untuk menentang relasi negara dengan pasar dalam globalisasi. Berangkat dari posisi tersebut tulisan ini berargumen bahwa interkoneksi dalam globalisasi menimbulkan paradoks dari konsep power . Internkoneksi antara pemilik modal membentuk standar nilai kapitalistik, namun vis-a-vis dengan hal ini resistensi juga muncul dalam skala global. Studi kasus yang digunakan adalah kemunculkan Gerakan Occupy Wallstreet di tahun 2011.Kata Kunci: globalisasi, resistensi, gerakan occupy wallstreet, power, interkoneksi DOI : https://doi.org/10.33005/jgp.v8i01.2169